2022
DOI: 10.18267/j.cebr.284
|View full text |Cite
|
Sign up to set email alerts
|

Employees' Digital Competency Development in the Construction and Automotive Industrial Sectors

Abstract: Nowadays, many companies make a great deal of effort to take full advantage of digital transformation and stay ahead of their competitors. The influence of digitalisation on manpower development and human capabilities as well as on the business environment, in general, is especially noticeable in the construction and automotive sectors. That is why the main purpose of this paper is to evaluate the impact of new digital technologies on employee competency development in Czech construction and automotive compani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Despite that digitalisation in construction may have been accelerated due to the pandemic (Mazurchenko and Zelenka, 2022) (Mazurchenko et al, 2020), drive financial incentives (Ninan et al, 2022), and prioritise feedback (Shojaei et al, 2022). However, the organisational influence on the adoption of innovation remains a complex interaction, and the understanding of it is limited across the construction context (Lin and Yi, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Despite that digitalisation in construction may have been accelerated due to the pandemic (Mazurchenko and Zelenka, 2022) (Mazurchenko et al, 2020), drive financial incentives (Ninan et al, 2022), and prioritise feedback (Shojaei et al, 2022). However, the organisational influence on the adoption of innovation remains a complex interaction, and the understanding of it is limited across the construction context (Lin and Yi, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Creating a digitally qualified workforce and changing the employees' mind-set for adapting to new tools and methods of digital work are still a significant obstacle, which often requires extensive training and development programs (Mazurchenko & Zelenka, 2021). Cyber security and data protection are great challenges as the automotive companies depend increasingly on digital technologies, meaning that they need robust security measures to protect their data and digital systems (Brandtner, Mayrboeck & Zimmermann, 2022).…”
Section: Critical Success Factors In Digital Transformation Projects ...mentioning
confidence: 99%
“…In general, this was empirically analyzed in several studies but limited in terms of research contexts. This issue was examined in the context of dynamic and complex industries, including manufacturing (Rajiani et al, 2016;Para-Gonzalez et al, 2018), automotive (Mazurchenko & Zelenka, 2022), start-ups (Jebali & Meschitti, 2020), IT (Mauro et al, 2020). In addition, the research was conducted in small and medium-sized enterprises (Llinas & Abad, 2020;Parwita et al, 2021;Sun & Mamman, 2022).…”
Section: Industry Concentrationmentioning
confidence: 99%
“…In particular, attention is paid to various training programs that strengthen employees' capabilities, which are important for creating organizational innovations (Lu et al, 2015). This means digital competence (Mazurchenko & Zelenka, 2022) that refers to knowledge, skills and attitudes towards the use of digital tools and solutions by employees. For example, Mazurchenko and Zelenka (2022), analyzing organizations from the automotive industry in the Czech Republic, concluded that the widespread use of digital technologies could definitely contribute to enhancing digital competences of employees, and thus to generating the potential for innovation.…”
Section: Innovation-driven Hrmp: Individual Levelmentioning
confidence: 99%
See 1 more Smart Citation